Two Book Reviews - Craig B. Howley; Aimee Howley; Kent P. Scribner (Arizona State University, 1994)
This issue of the Education Policy Analysis Archives comprises two book reviews: An essay review of R. G. Brown Schools of Thought by Craig Howley and Aimee Howley, and a review of Ernest R. House, Professional Evaluation by Kent P. Scribner.